PENERAPAN IPTEK PADA INDUSTRI KECIL PEMBUATAN TELUR ASIN KHAS TAMBAKREJO KOTA SEMARANG - Sunyoto, Sunyoto; Suwahyo, Suwahyo; Putri, Meddiati Fajri (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2015)
The objectives of science and technology for the community (IbM) is to resolve the problems faced by small industries making salted eggs in Tambakrejo, Semarang. The main problem is in the produce of salted egg takes a long time (14 days) and marketing are still limited. Implementation team is lecture and students with expertise appropriate to the needs of the field. In making appropriate technology equipment in the workshop of Department of Mechanical Engineering, Engineering Faculty, Semarang State University. The results of these activities, among others, a set of tools salted egg maker with pressure (UPSE-Under Pressure Salted Egg) in which this tool can generate salted eggs within one-two days. In the aspect of management has produced an output in the form of salted egg packaging design in two partners and certificates P-IRT from the City Health Office Semarang.